In/Out: fictionalising autobiography in Vincent Dieutre's Jaurès (2012) (Studies in French cinema, 2017)
This article offers a close reading of Vincent Dieutre's 2012 production Jaurès. It presents the film as the continuation of a sustained autobiographical filmmaking practice in which individual experience provides the perspective from which to consider experience more generally. The article examines the way in which Dieutre presents what we see on screen in Jaurès as an archival inventory of the ephemeral rhythms of the past. The article moves on to question what happens when this inventory becomes avowedly fictive, identifying in Dieutre's filmmaking an impulse that moves from a forensic gesture of temporal retrieval to one of fictionalised reinterpretation and restaging. Dieutre asks the spectator to participate in a mode of remembrance that treads the line between fiction and reality as a means of giving a more malleable and reflective account of experience. This article shows how Dieutre constructs a filmic poetics based on showing and hiding that allows him to explore the mechanisms of social definition that shape and control both public and private identities.
https://katalog.adlr.link/Record/ai-68-OLC1999738853